The Role of Advocates in Children's Cases in the Juvenile Criminal Justice System in Indonesia - Kamal, Maulana; Agus, Muhamad Arif; Anwar, Umar (Polteknik Ilmu Pemasyarakatan, 2025)
The Laws and Regulations governing the Juvenile Criminal Justice Process are still discriminatory against Juvenile Law Enforcers, because there are requirements to become a Special Child Advocate as with other Law Enforcers who must be certified as Juvenile Law Enforcers. This study aims to analyze the requirements for advocates in child cases in the juvenile criminal justice system and the requirements for advocates in child cases in the juvenile criminal justice system in the future. The research method uses a normative legal approach method by conducting a study of the law. The results of the study show that Advocates in Child Cases in the Juvenile Criminal Justice System are not burdened with special requirements related to the specificity of children like other law enforcers and Advocates in the future must have an interest, attention, dedication, and understand the problems of Children and have attended technical training on Juvenile justice as a requirement to become a child advocate. This is to ensure the specialization of Advocates in the future as realizing the expression,